Tech firms tackle fake accounts and political hackers. Issue 9 (September 2018) - Unknown
Abstract : While coming under a barrage of criticism over their apparent unwillingness to combat 'fake news' and election meddling, tech firms have taken some steps to combat misuse of their platforms.